GC-on-chip: integrated column and photoionization detector. Issue 7 (7th April 2015) - Akbar, M.; Shakeel, H.; Agah, M.
<x xml:space="preserve">Abstract</x> We present a GC-on-chip module capable of providing highly efficient separation and ultra-sensitive detection of volatile organic compounds on a single platform.